2015
DOI: 10.3892/etm.2015.2263
|View full text |Cite
|
Sign up to set email alerts
|

Marchiafava-Bignami disease with rare etiology: A case report

Abstract: A male, 62-year-old patient was admitted to hospital due to dizziness and gait disturbance for 10 days. The patient had fallen a few times due to the gait instability, which was associated with stiffness and memory loss. The patient had undergone cardiac carcinoma surgery three years previously and had no drinking history. Physical examination revealed that the patient was lucid when conscious but exhibited slurred speech, apathy and cognitive impairment. The finger-to-nose and rapid alternating movement tests… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…In one case of hyperemesis gravidarum, MR revealed edema in the splenium of corpus callosum, and abnormal signals in the thalamus around the third ventricle, head of caudate nucleus, and insula (Wernicke's encephalopathy); above symptoms were completely improved after administering VitB1 [7]. The splenium of corpus callosum was involved in other three patients with short-term eating disorders, and their prognoses were good after administering B vitamins [8]- [10]. 2) Diabetes: seven patients in this group were combined with diabetes, including above-mentioned two patients who died (blood glucose control is unknown).…”
Section: Discussionmentioning
confidence: 95%
“…In one case of hyperemesis gravidarum, MR revealed edema in the splenium of corpus callosum, and abnormal signals in the thalamus around the third ventricle, head of caudate nucleus, and insula (Wernicke's encephalopathy); above symptoms were completely improved after administering VitB1 [7]. The splenium of corpus callosum was involved in other three patients with short-term eating disorders, and their prognoses were good after administering B vitamins [8]- [10]. 2) Diabetes: seven patients in this group were combined with diabetes, including above-mentioned two patients who died (blood glucose control is unknown).…”
Section: Discussionmentioning
confidence: 95%
“…The exact underlying etiology and pathophysiology still remain unclear. However some studies have suggested a number of risk factors including Lead toxicity, neoplasm, vitamin B complex deficiency, or osmotic disorders [ 1 ]. In our case we did not observe any history of neoplastic diseases and laboratory tests showed no Lead toxicity or vitamin B12 deficiency.…”
Section: Discussionmentioning
confidence: 99%
“…MBD is classically characterized by acute edema and necrosis of corpus callosum and subsequent symmetric demyelination and atrophy of this structure. The exact etiology of the disease is still under investigation [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
“…Multi-disciplinary studies including functional neuroimaging and electrophysiological recording, namely PET, fMRI and BCI, have also been performed in our laboratory (66,67). In addition, our group has established cooperation among research institutes and non-governmental organizations to promote the welfare of DOC patients, with an ultimate goal of establishing the first DOC society in China.…”
Section: Resultsmentioning
confidence: 99%